Synthesis of White Silica From “Joha Rice Husk” (A Special Rice Variety of Assam, India), Characterization and Determination of Its Point of Zero Charge (pHPZC) - Jyotirmoy Sarma; Sanchayita Rajkhowa; Sourav Das (Journal of Chemistry)
In this study, the rice husk (RH) of “Joha rice” a unique rice variety of Assam (Northeast India) has been used as raw materials for synthesis of ash and silica powder. The combustion of the husk at 500°C for 1 h followed by further treatment at 800°C for 2 h in muffle furnace produces white rice husk ash (RHA). One part of RHA was kept as untreated, and the another part was acid treated. Silica was extracted from the untreated ash in the form of sodium silicate by treating with 2.5M NaOH at the boiling temperature. Then, silica was precipitated from sodium silicate by slow addition of 2.5M H2SO4. The broad x-ray diffraction (XRD) pattern and characteristic peaks at d-spacing, 8.3792 and 4.1489 with specific 2θ at ∼21.3° reveal the presence of amorphous SiO2 as major phase in the ash (both acid treated and untreated). The characteristic Fourier transform infrared (FTIR) spectroscopic peaks at 470–450, 801, and 1100 cm−1 for different modes of Si-O-Si vibrations also support the presence of silica. The scanning electron micrographs (SEMs) revealed the morphology of the RHA as fine particles undergoing agglomeration probably due to hydrogen bonding between surface silanol groups present. The irregular rough morphology is a characteristic of the amorphous nature of the samples. The energy-dispersive X-ray analysis (EDX) showed that RHA composition was dominated by elements Si and O for both untreated and acid-treated samples. For acid-treated sample, the amount of Si and O is found to be comparatively higher than the untreated one due to surface cleaning. The point of zero charge (pHPZC) of the prepared samples was determined by a simple pH metric method. The pHPZC of the untreated RHA was found to be ∼ 9.8 ± 0.2. However, almost similar pHPZC values of the acid-treated RHA silica and commercial silica (∼6.6 ± 0.2) indicate the effectiveness of acid treatment prior processing.